(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To investigate the characteristics of white blood cell indices in patients with depression. Subjects and methods: A cross-sectional descriptive study was conducted on 107 inpatients diagnosed with a depressive episode at Bach Mai Hospital from March 2025 to October 2025. Results: The majority of patients were female (76.64%), and the most prevalent age group was over 60 years old (32.71%). Most patients were admitted with severe depression (89.72%), with high rates of suicidal ideation/behaviors (61.68%) and psychotic symptoms (28.04%); the remaining patients presented with moderate depression (10.28%). Regarding general white blood cell indices: the mean total white blood cell count (7.81 ± 2.40 G/L) and specific leukocyte subsets were all within normal reference ranges. However, patients with psychotic symptoms exhibited significantly higher neutrophil counts compared to those without psychotic symptoms. This elevation was most pronounced in the group with complex clinical presentations (combined delusions and hallucinations), showing increased levels in total WBC count, neutrophil count, and the neutrophil/lymphocyte ratio. Conclusion: Elevated white blood cell counts were observed in patients with a depressive episode with psychotic features